Sztuka rozumienia i sztuka widzenia. Dwie rozmowy – z Danutą Danek i Krzysztofem Hejkem - Redakcja (Wydawnictwo Naukowe UAM, 2013)
Two interviews: ”The art of understanding”, with the professor of literary history, Danuta Danek, and “The art of seeing”, with the professor of art photography, Krzysztof Hejke, are connected with the issue of the publication of the manuscript written in 1849 by an outstanding writer Stanisław Morawski (1802–1853) preserved in the Polish Library in Paris, entitled “Memoires about Maria Szymanowska” (containing, among other things, a romantic treatise on music, unknown till now), as well as with the set of art photographs taken in Lithuania, in the land estate of the writer.
The art of understanding and the art of seeing. Two interviews: with Danuta Danek